Pengaruh Budaya Organisasi, Komitmen Organisasi, dan Pelatihan Kerja Terhadap Kinerja Karyawan BPR Dana Nusantara di Kota Batam - Aurelia Glorianne; Mauli Siagan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to assess the extent to which organizational culture, organizational commitment, and job training contribute to improving employee performance at BPR Dana Nusantara located in Batam City. Data were obtained through the distribution of questionnaires to 104 respondents, which included all employees of BPR Dana Nusantara in Batam City. Data analysis methods included descriptive statistical testing, validity, reliability, classical assumptions, and multiple linear regression using SPSS software version 30. The research findings revealed that organizational culture, organizational commitment, and job training partially influence employee performance. Furthermore, simultaneous testing showed that these three variables simultaneously influence employee performance. Analysis of the coefficient of determination indicates that variations in employee performance can be explained by these three independent variables, while the remainder is influenced by external factors outside the research model.